Sedentary Lifestyle as a Leading cause of Some Diseases and Disability - Tri Tjahjono, Cholid; Arthamin, Maimun (Universitas Brawijaya, 2024)
The prevalence of inactive lifestyles has increased, leading to detrimental effects on health. Sedentary behavior refers to any action that involves extended periods of sitting, reclining, or lying down and requires minimal energy expenditure. Insufficient physical activity is prevalent among one-third of the global population aged 15 years and older, leading to adverse health effects. Nevertheless, there is a lack of awareness regarding the health hazards associated with sedentary behaviors. The prevalence of sedentary lifestyles is expanding globally due to limited opportunities for physical activity, the rise in sedentary work environments including office jobs, and the growing prevalence of television and video devices. As a result, the related health issues are increasing. Sedentary behaviors have a broad range of negative effects on the human body, including an increased risk of death from any cause, death from cardiovascular disease, cancer, and metabolic disorders such as diabetes mellitus, hypertension, and dyslipidemia. They also increase the risk of musculoskeletal disorders like arthralgia and osteoporosis, as well as depression and cognitive impairment. Therefore, minimizing sedentary behaviors and boosting physical exercise are both vital to promote public health.